Economic development - Michael P Todaro; Smith, Stephen C (Chennai Pearson, 2023)
Economic Development, - the leading textbook in this field - provides students with a complete and balanced introduction to the requisite theory, driving policy issues, and latest research. Todaro and Smith take a policy-oriented approach, presenting economic theory in the context of critical policy debates and country-specific case studies, to see how theory relates to the problems and prospects of developing countries.
Keywords: Economic Development